2017
DOI: 10.1149/2.0251701jss
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Ytterbium in Calcium and Strontium Zirconate Matrices

Abstract: A series of ytterbium substituted calcium and strontium zirconates of nominal composition, MZr1-xYbxO3-δ (M = Ca, Sr & x = 0 – 0.2) was synthesized by solid state reaction. Limits of solid solution formation of ytterbium were established in both the matrices. The contrasting roles played by ytterbium toward grain growth and oxide ion conductivity in these matrices were explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Further, in the high temperature region (above 600 • C), the conductivity of grain bulk does not change with humidity, while at lower temperatures, it increases with a rise of pH 2 O as can be seen in Figure 5. It is worth noting that the total conductivity of Sr x Zr 0.95 Yb 0.05 O 3-δ (x = 1.00) obtained in the present research is similar to that of the same composition measured in air and reported in [22]. The literature data are presented in Figure 5a for comparison.…”
Section: Electrical Conductivity Of Srxzr095yb005o3-δsupporting
confidence: 89%
See 2 more Smart Citations
“…Further, in the high temperature region (above 600 • C), the conductivity of grain bulk does not change with humidity, while at lower temperatures, it increases with a rise of pH 2 O as can be seen in Figure 5. It is worth noting that the total conductivity of Sr x Zr 0.95 Yb 0.05 O 3-δ (x = 1.00) obtained in the present research is similar to that of the same composition measured in air and reported in [22]. The literature data are presented in Figure 5a for comparison.…”
Section: Electrical Conductivity Of Srxzr095yb005o3-δsupporting
confidence: 89%
“…The solubility limit of ytterbium in SrZr 1-x Yb x O 3-δ was reported to be about 5 at. %, and the conductivity was shown to increase with an increase in Yb concentration, reaching a maximal value for the SrZr 0.95 Yb 0.05 O 3-δ composition [22]. However, to the best of our knowledge, the influence of Sr content on the conducting properties of this perovskite have not yet been studied.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation